A Compact Dual-Band Circularly Polarized Antenna with Wide HPBWs for CNSS Applications. (4th March 2018) - Li, Chao; Zhang, Fu-Shun; Zhang, Fan; Yang, Kaiwen
Abstract : A compact dual-band circularly polarized antenna with wide half-power beamwidths (HPBWs) for compass navigation satellite system applications is proposed in this paper. The CP radiation is realized by arranging four compact dual-band inverted-F monopoles symmetrically to the center point, where the four monopoles are excited with a 90° phase offset through a compact sequential-phase feeding network. The compactness of the dual-band inverted-F monopole is realized by inserting two chip inductors in the horizontal portion of the monopole. The overall dimension of the antenna is only 0.211 λ 0  × 0.211 λ 0  × 0.057 λ 0, where λ 0 is the corresponding free-space wavelength at 1.268 GHz. Experimental results show that the proposed antenna exhibits two overlapped impedance and axial ratio bandwidths of 50 MHz (1.236–1.286 GHz) and 40 MHz (1.532–1.572 GHz). Wide HPBWs of about 120°/125° and 121°/116° (XOZ/YOZ planes) at center frequencies (1.268, 1.561 GHz) of the CNSS-2 B3 and B1 bands are obtained, respectively. With these good performances, the antenna can be a good candidate for CNSS applications.